Efficient and high-power subsea bubble energy harvesting by controlling flow pattern. (February 2023) - Guan, Zhibin; Li, Ping; Wen, Yumei; Du, Yu; Wang, Guoda
Abstract: The bubble energy harvesting system can effectively convert the subsea gas potential energy into electrical energy for the subsea observation equipment, but a high gas–liquid two-phase flow velocity will lead to excessive energy loss. Here, we analyzed the relationship between intake gas flow rate and flow velocity, and assessed the energy conversion efficiency and output power of various flow patterns caused by the reduction of the flow velocity. A flow pattern control scheme is proposed to adjust the gas–liquid two-phase flow velocity by quantitatively releasing bubble, allowing the energy harvesting system to maintain high output power and high efficiency. The results indicate that slug flow is the most efficient flow pattern for energy harvesting. In the experimental system with an effective height of 1.6 m, slug flow with a quantitatively released gas volume of 0.3 L can generate an energy density of 134 J/m 3 and a maximum output power of 140 mW. This research on slow gas–liquid flow patterns guides the development of long-term, continuous, and stable subsea in-situ energy supply systems. Highlights: The relationship between gas flow rate and flow velocity for energy harvesting is analyzed. The flow patterns in the bubble energy harvesting system are determined for the first time. A flow pattern control scheme with high efficiency and high power is proposed. The slug flow, with the highest energy density, is the best flow pattern for harvesting.